Carotid artery web and ischemic stroke: A case-control study. (3rd January 2017) - Coutinho, Jonathan M.; Derkatch, Sheldon; Potvin, Alphonse R.J.; Tomlinson, George; Casaubon, Leanne K.; Silver, Frank L.; Mandell, Daniel M.
Abstract : Objective: To determine whether there is an association between carotid artery web and ischemic stroke. Methods: This was a single-center, age- and sex-matched, case-control study. Cases were consecutive patients with anterior circulation ischemic stroke of undetermined etiology (Trial of Org 10172 in Acute Stroke Treatment [TOAST] classification). Controls were consecutive patients with cerebral aneurysms, arteriovenous malformations, or primary intracerebral hemorrhages. Additional inclusion criteria were age <60 years and CT angiography of the neck. Two neuroradiologists diagnosed webs according to previously published criteria. One neuroradiologist also assessed for nonstenotic atherosclerotic plaque (carotid wall thickness ≥3 mm or intramural calcification). We used conditional logistic regression to estimate the odds ratio between carotid web and ischemic stroke and its 95% confidence interval. Results: Fifty-three of 62 cases (85%) were matched by age (within 1 year) and by sex to 102 controls. There was a carotid web in 4 of 53 cases (9.4%) vs 1 of 102 controls (1.0%, odds ratio = 8.0, 95% confidence interval = 1.2–67, p = 0.032). There was no significant difference in the prevalence of nonstenotic carotid atherosclerotic plaque between the case and control groups. There was agreement on diagnosis of web for 163 of 164 patients (99%) and 7 of 8 webs (88%), and the Cohen κ for interobserver agreement was 0.93. Conclusions: There is an association between carotid artery web and ischemic stroke in patients who lack an alternative cause of stroke. Carotid web may be an underappreciated risk factor for stroke.